Experimental study on mafic rock dissolution rates within CO2-seawater-rock systems. (1st March 2020) - Marieni, Chiara; Matter, Juerg M.; Teagle, Damon A.H.
Abstract: Far-from-equilibrium batch experiments have been performed to study the low temperature dissolution potential of crystalline submarine basalts (from Juan de Fuca Plate and Mid-Atlantic Ridges) and of a highly altered gabbro from the Troodos ophiolite (Cyprus) in presence of seawater and carbon dioxide (CO2 ). The experiments have been carried out at 40 °C for up to 20 days with initial pH of ∼4.8 and under ∼1 bar pCO2 to identify the progressive water-rock interactions. Elemental steady-state release rates from the rock samples have been determined for silicon and calcium, the solution concentrations of which were found to be the most effective monitors of rock dissolution. Mass balance calculations based on dissolved Si and Ca concentrations suggest the operation of reaction mechanisms focussed on the grain surfaces that are characteristic of incongruent dissolution. Also, basic kinetic modelling highlights the role of mass-transport limitations during the experiments. Ca release rates at pH ∼ 5 indicate significant contributions of plagioclase dissolution in all the rocks, with an additional contribution of amphibole dissolution in the altered gabbro. Si release rates of all solids are found to be similar to previously studied reactions between seawater and basaltic glass and crystalline basalt from Iceland, but are higher than rates measured for groundwater-crystalline basalt interaction systems. This comparison with previous experimental results resumes the debate on the role of experimental variables, such initial rock mass and crystallinity, pCO2, and fluid chemistry on dissolution processes. Our new data suggest that CO2 -rich saline solutions react with mafic rocks at higher rates than fresh water with low pCO2, at the same pH. Most significantly, both ophiolitic gabbro and Juan de Fuca basalts show Si and Ca release rates similar or higher than unaltered crystalline basalt from Iceland, highlighting the potential substantial role that ophiolitic rocks and offshore mafic reservoirs could play for the geological storage of CO2 .